Implementasi Sistem Informasi Lomba Kompetensi Siswa SMK (LKS SMK) Tingkat Nasional Pada Satuan Kerja Direktorat Pembinaan SMK Kemdikbud - Nurfahmi, Ifan (Universitas Pamulang, 2023)
Every year, the Directorate of Vocational School Development organizes the National Vocational School Student Competency Competition (LKS SMK) aimed at continuously motivating students to enhance the quality of their competencies. It also serves as a platform to showcase vocational school graduates with excellent qualifications ready to enter the world of business and industry (DUDI). This initiative is an implementation of Presidential Instruction number 9 of 2016 concerning the Revitalization of Vocational Schools. Throughout the process of the National Vocational School Student Competency Competition (LKS SMK), various issues arise. Initially, there was no system facilitating the organizing committee to manage participant registration data, leading to discrepancies in the data. Additionally, there was a lack of a transparent system to oversee the competition, resulting in confusion due to errors in the accumulation of competition results. To address these issues, the development of an information system was necessary to bridge the gap between organizers and participants. The methodology used for this development was the waterfall model, incorporating visual UML (Unified Modeling Language) modeling. The outcome of this research is a web-based application developed using the PHP programming language, with data storage facilitated by MySQL.